Case Report: Dupilumab in difficult-to-treat bullous pemphigoid at the University Hospital Schleswig-Holstein, Campus Kiel - Mehrjerdian, Y.; Atallah, R.; Wijaya, B.; Hammers, C. M.; Gerdes, S.; Heine, G. (Frontiers in Medicine, 2026)
Bullous pemphigoid (BP) is the most common autoimmune blistering disease affecting the skin. It is characterized by a type 2 immune-mediated pathogenesis. BP predominantly affects elderly patients who have multiple comorbidities, and treatment can be particularly challenging in refractory cases or when standard immunosuppressive therapies are limited due to toxicity or contraindications. Here, we present a case series of five patients with confirmed BP who were treated with off-label dupilumab. All five patients achieved sustained clinical improvement with dupilumab treatment, including reductions in disease activity and pruritus. No severe adverse events were reported, except for one case of manageable conjunctivitis. Dupilumab was well tolerated and resulted in marked clinical benefit in all five BP patients included in this case series. These findings support the growing evidence for dupilumab’s potential role as a safe and effective treatment option for BP. Further long-term clinical trials are needed to assess its disease-modifying potential.